2011
DOI: 10.1080/15252019.2011.10722180
|View full text |Cite
|
Sign up to set email alerts
|

Spreading the Virus

Abstract: Viral advertising has attracted advertisers in recent years, yet little is known about how exactly it works from an information processing perspective. This study extends knowledge by exploring how the emotional tone (pleasant, unpleasant, coactive) of viral video ads affects attitude toward the ad, attitude toward the brand, and forwarding intentions. Results indicate that pleasant emotional tone elicits the strongest attitude toward the ad, attitude toward the brand, and intention to forward. The effects wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(72 citation statements)
references
References 29 publications
4
63
0
Order By: Relevance
“…Therefore, surprise and happiness are remarkable emotions in the sample of the most widely shared viral video ads, and this coincides with the contributions of Teixeira (2012), Dobele et al (2007) or Eckler and Bolls (2011) in this regard.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Therefore, surprise and happiness are remarkable emotions in the sample of the most widely shared viral video ads, and this coincides with the contributions of Teixeira (2012), Dobele et al (2007) or Eckler and Bolls (2011) in this regard.…”
Section: Discussionsupporting
confidence: 72%
“…On the other hand, and related to all of the above, the analysis of the final emotional tone conveyed by these ads shows that all viral videos in the Top 25 ranking can be classified as «agreeable», which coincides fully with the results of Eckler and Bolls (2011).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Along the same lines, Berger and Milkman (2012) found that positive news articles invited more frequent email-based retransmissions than those with negative emotional valence. An experimental study by Eckler and Bolls (2011) also demonstrated that video ads with positive emotional tone are more likely to be retransmitted than those with negative tone (see also Carter, Donovan, & Jalleh, 2011). However, in a study in the political context of a German election, Dang-Xuan et al, (2013) found that “tweets” of emotional evocative information, whether positively or negatively toned, tended to be retweeted with greater frequency than less emotionally intense information (see also Berger & Milkman, 2012; C.…”
Section: Message or Information Factorsmentioning
confidence: 95%
“…Current research on how emotion influences the decision to share content broadly indicates that content that generates a strong emotional impact on individuals, regardless of whether the impact is positive or negative, is most likely to become viral (Berger & Milkman, 2012;Berger, 2011;Heath, 1996;Heath, Bell & Sternberg, 2001;Peters, Kashima & Clark, 2009). More specifically, research studies by Berger & Milkman (2012); Dobele et al (2007); Eckler & Bolls (2011);Guadagno, Rempala, Murphy & Okdie (2013) and Teixeira (2012) suggest that, in a more specific way, content that conveys pleasurable emotions such as surprise or joy increases the chances of viralization. Most of these studies are within the field of reception and reflect the perceptions of subjects who are exposed to certain selected messages and state their intention whether to share these messages with their contacts or not.…”
Section: Introductionmentioning
confidence: 99%